Gallic acid against hepatocellular carcinoma: An integrated scheme of the potential mechanisms of action from study - Hadeer A Aglan; Hanaa H Ahmed; Sayed A El-Toumy; Nadia S Mahmoud (Tumor Biology)
The global burden of hepatocellular carcinoma is increasing; actually, it is estimated as 750,000 new cases annually. This study was initiated to emphasize the possibility that gallic acid could alleviate hepatocarcinogenesis in vivo . In this study, 40 rats were enrolled and distributed as follows; group 1 was set as negative control, while all of groups 2, 3, and 4 were orally received N -nitrosodiethylamine for hepatocellular carcinoma induction. Group 2 was left untreated, whereas groups 3 and 4 were orally treated with gallic acid and doxorubicin, respectively. The current data indicated that gallic acid administration in hepatocellular carcinoma bearing rats yielded significant decline in serum levels of alpha-fetoprotein, glypican-3, and signal transducer and activator of transcription 3 along with significant enhancement in serum suppressors of cytokine signaling 3 level. Also, gallic acid–treated group displayed significant downregulation in the gene expression levels of hepatic gamma glutamyl transferase and heat shock protein gp96. Intriguingly, treatment with gallic acid remarkably ameliorated the destabilization of liver tissue architecture caused by N -nitrosodiethylamine intoxication as evidenced by histopathological investigation. In conclusion, this study demonstrates that the hepatocarcinogenic effect of N -nitrosodiethylamine can be abrogated by gallic acid supplementation owing to its affinity to regulate signal transducer and activator of transcription 3 signaling pathway through its outstanding bioactivities including antioxidant, anti-inflammatory, apoptotic, and antitumor effects.